THE RELATIONSHIP OF SALT CONSUMPTION WITH THE OCCURANCE OF HYPERTENSION IN THE ELDERLY ON THE VILLAGE OF KAWENGEN SUB. EASTERN UNGARAN DISRICT OF SEMARANG - STIKES DUTAGAMA KLATEN (STIKES DUTAGAMA KLATEN, 2014)
Background: hypertension is a condition where a person experiences an increase in blood pressure. Hypertension is caused by various factors that influence one another. One of the factors of the causes of hypertension is the consumption of excess fat and salt. From the observations obtained as many as 15 people have hypertension hypertension salt intake, as many as 30 people consume salt and hypertension stage 1 and the remaining 20 people consume salt and stage 2 hypertension (Adib, 2009). Purpose: to determine the relationship of salt intake to hypertension in the elderly in the village Kawengen, East Unggaran district, Semarang regency. Research methods: the type of research that used analytic correlation with cross-sectional design of the study is to determine the relationship of salt intake to hypertension in the elderly in the village Kawengen, East Unggaran district, Semarang regency. The samples are 96 respondents with purposive sampling technique. Analysis used Spearman Rank correlation (Rho).Results: the results of the study found a significant relationship between salt intake to hypertension in the elderly in the village Kawengen, East Unggaran district, Semarang regency with a value of 6.93 t count> t table 2.000 and P-value = 0.000 <0.05 (5% ). Conclusion: There is a significant relationship between the two variables, consumption of salt with hypertension in the elderly in the village Kawengen, Unggaran kecamtan East, Semarang regency.